RELATIONSHIP BETWEEN TRANSITION MONOID AND MINIMAL STATE AUTOMATON TO IDENTIFY GENETIC MUTATIONS ON ,B-GLOBIN GENE IN THALASSEMIA DISEASE - Fitri Ferdania, Devi
/)-Thalassemia is an autosomal recessive blood disorder characterized by abnor malities in the synthesis of the /) globin gene. Together with a globin gene, /) globin gene is a subunit of globin protein, called Haemoglobin, located inside our red blood cells to deliver oxygen from the lungs to all of the tissues throughout our body. Thereby, individuals with /)-Thalassemia will often feel limp due to a lack of oxygen dissolved in their blood. 1n this Final Project, I have constructed a finite state automaton to detect and clasify /) globin-gene mutation using its DNA sequence. Finite state automata have a close connection to an algebraic structure, that is a monoid. Together with the theory of syntactic monoid, I presents a method ology to minimize the numbers of the internal state of an automaton to have minimal automata. So that we can construct a minimal automaton to detect /) globin-gene mutation causing /)-Thalassemia disease. 1n the end, I have developed a Matlab program to simulate it.